Public Relations and Corporate Reputation in The Era of Industrial 4.0: A Systematic Literature Review - Ramdina, Vika (Magister of Communication Science, Sahid University Jakarta., 2025)
The most important topic in corporate studies is public relations (PR) and/or corporate reputation, which informs relevant stakeholders about present and future business activities. Relying on traditional channels would be considered foolish in the digitalization era or Industrial 4.0 since corporate information sent through these channels is slow in comparison to the quick processes via social media. By spotting pattens in research and publication production, the study seeks to investigate and provide light on corporate reputation in the age of industrial 4.0. To identify the rising themes of corporate reputation, a systematic literature review (SLR) was conducted utilizing bibliometric analysis of previous studies from 2010 to 2022. Wstern countries were shown to be still the most productive nations in research of this field in 2011. The bibliometric analysis's conclusions also suggested that corporate image, credibility, engagement, and crisis communication might be new research topics. Therefore, after identifying several possible themes to be further evaluated related business reputation in I4.0 in subsequent research, this study offers insightful information to scholars and practitioners.